Firm size implications for environmental sustainability of supply chains: evidence from the UAE. Issue 5 (22nd April 2020) - Balasubramanian, Sreejith; Shukla, Vinaya; Chanchaichujit, Janya
Abstract : Purpose: Effective environment and climate change management require supply chain-wide focus (from the initial design to the end-of-life management) as well as universal participation and commitment of firms. However, the environment-related role and contribution of different sized firms in the supply chain are unclear from previous research which this study seeks to clarify using the context of UAE's construction sector. Design/methodology/approach: Using data collected from a structured survey (455 responses) and semi-structured interviews with 20 key supply chain stakeholders, this study analyses and understands hypothesized differences between small and medium firms (SMEs) and large firms on three key supply chain environmental sustainability aspects: the extent of green supply chain practices (GSCP) implemented, the strengths/influences of drivers and barriers affecting the implementation of GSCP, and the associated environmental, cost-related and organizational performance benefits derived from GSCP. Findings: Large firms were found to show significantly greater levels of implementation of GSCP, greater internal drive for implementation and lower barriers to implementation than SMEs. SMEs though were found to be not too far behind large firms with regards to the environmental, cost-related and organizational performance benefits from GSCP implementation. Practical implications: Findings from this study is useful for benchmarking the GSCP implementation of large firms and SMEs, influences of drivers and barriers affecting the implementation of GSCP and associated performance benefits derived from GSCP implementation. Policymakers and practitioners could use the study findings to develop suitable policies/interventions so as to ensure that all firms irrespective of their size can contribute equitably towards improving the environmental sustainability of supply chains. Originality/value: This study is arguably the first comprehensive attempt to understand how various environmental sustainability aspects in supply chains are perceived and performed by SMEs and large firms.